El viaje de Federico a la luna : en torno al guión cinematográfico de Federico García Lorca - Dobos, Erzsébet (Acta Hispanica, 2009)
This essay is about Federico García Lorca’s filmscript, Trip to the Moon written during his stay in América between June of 1929 and March of 1930. Although there was no doubt about the existence of this script the matter of fact is that was found only in 1989.The surrealist text is surprisingly daring, in certain way more than Buñuel’s Un chien andalou. For the reading and correct interpretation of the text is essential to be familiar with Lorca’s biografical background and system of symbols.The point of this essay is explain the reason and the meaning of the script and its importance in Lorca’ oeuvre.To sume it up, the message is dark: in Lorca’s view the well balanced, harmonious relationship betwen man and women does not exist or is sentenced to death and ends up in the death which means moon, according Lorca’s symbols.